Gene expression analysis of vastus medialis cells after tourniquet-induced ischemia during total knee arthroplasty: a randomized clinical trial - Jawhar, Ahmed; Brenner, Desiree; Torre, Carolina de la; Sticht, Carsten; Obertacke, Udo; Ponelies, Norbert (European journal of trauma and emergency surgery, 2021)
Postoperative quadriceps muscle strength was lowered after tourniquet application during total knee arthroplasty (TKA). Furthermore, tourniquet application results in higher proteolytic activity within vastus medialis cells, without influence on the amount and function of mitochondria. The effects of the commonly utilized intraoperative tourniquet on gene expression within the human skeletal muscle cells are barely examined. The purpose of the present study was to analyze the gene expression within the skeletal muscle cells after tourniquet-induced ischemia to identify differential expressed genes (DEGs) and pathways.
Gesehen am 19.04.2021
Published online: 5 August 2019